Debate Based on Inquiry Learning (DBOIL): Validitas Isi Model Pembelajaran untuk Meningkatkan Keterampilan Argumentasi Ilmiah Mahasiswa pada Pembelajaran Fisika - Hendratmoko, Ahmad Fauzi; Dewanti, Binar Ayu; Shofiyah, Noly; Septaria, Kiki (Universitas Negeri Surabaya, 2025)
Improving students' skills in scientific argumentation is an important initiative aimed at producing high-quality graduates. Debate Based on Inquiry Learning (DBOIL) is a learning model developed to facilitate the development of students’ scientific argumentation skills. This learning model is constructed based on the advantages of inquiry and debate, as well as a solution to the limitations of both in optimally improving scientific argumentation skills. As an intervention integrated into learning activities, DBOIL must satisfy criteria such as relevance (content validity), consistency (construct validity), practicality, and effectiveness. This study aims to describe the content validity of DBOIL. This is based on expert judgment, with 25 validators consisting of experts, lecturers, and education practitioners. The data collected in this study were analyzed using the Aiken Methodology (Aiken's V) which was strengthened by calculating the 95% confidence interval (95% CI). The results showed that the content validity of DBOIL has been proven valid. This shows that DBOIL is worthy of further research to explore and reveal other criteria, namely consistency, practicality, and effectiveness.